2017
DOI: 10.1371/journal.ppat.1006206
|View full text |Cite
|
Sign up to set email alerts
|

Precision engineering for PRRSV resistance in pigs: Macrophages from genome edited pigs lacking CD163 SRCR5 domain are fully resistant to both PRRSV genotypes while maintaining biological function

Abstract: Porcine Reproductive and Respiratory Syndrome (PRRS) is a panzootic infectious disease of pigs, causing major economic losses to the world-wide pig industry. PRRS manifests differently in pigs of all ages but primarily causes late-term abortions and stillbirths in sows and respiratory disease in piglets. The causative agent of the disease is the positive-strand RNA PRRS virus (PRRSV). PRRSV has a narrow host cell tropism, limited to cells of the monocyte/macrophage lineage. CD163 has been described as a fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
259
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(271 citation statements)
references
References 76 publications
8
259
1
3
Order By: Relevance
“…However, knocking out only CD163 in the pig is sufficient to render animals non-susceptible to PRRSV infection and replication [24,25,125]. It is proposed that following endocytosis, CD163 associates with the virus within the endosome, resulting in uncoating of the virus and the release of the viral genome into the cellular cytoplasm [126].…”
Section: Antibody Responsementioning
confidence: 99%
“…However, knocking out only CD163 in the pig is sufficient to render animals non-susceptible to PRRSV infection and replication [24,25,125]. It is proposed that following endocytosis, CD163 associates with the virus within the endosome, resulting in uncoating of the virus and the release of the viral genome into the cellular cytoplasm [126].…”
Section: Antibody Responsementioning
confidence: 99%
“…Cluster of Differentiation 163 (CD163) knockout pigs were generated by depleting CD163 complete protein or deletion of the region of CD163 gene, encoding SRCR5 through using CRISPR/Cas9 gene target and somatic cell nuclear transfer (SCNT) approaches, which confers the resistance to infection of numerous porcine reproductive and respiratory syndrome (PRRSV) isolates in cultured cells or pigs. It was confirmed by correct folding and expression of SRCR5 removal CD163 on macrophages surface and biological activity of hemoglobin hapto-globin scavenger Burkard et al, 2017).…”
Section: Crispr On the Farmmentioning
confidence: 71%
“…A previous report showed that the phosphorylation of the N protein could impair the viral replication ability in Marc-145 cells (Chen et al, 2018a;. However, since PAMs cells play an important role during the PRRSV infection (Burkard et al, 2017), we questioned whether the growth curve of viruses in PAMs was similar to that in Marc-145 cells. In this study, viruses were incubated with the PAMs at an MOI of 0.1.…”
Section: The Identified Phosphorylation Modification Of the N Proteinmentioning
confidence: 92%